The influence of cultivation conditions on biosynthetic ability of Eremothecium ashbyi Guillierm. - Поліщук, Валентина Юріївна; Дуган, Олексій Мартем’янович (Technology audit and production reserves, 2016)
Despite the extremely poor riboflavin amount in the food for people and animals and its important role in the biochemical processes of metabolism, yet little attention is paid to the production of vitamin B2 by biotechnological means. Therefore, the main aim is to study an impact of physical and chemical parameters of fermentation and various power sources of ascomycetes Eremotecium ashbyi to producing the desired product. The main biosynthetic indicators of E.ashbyi culture, which were defined in the fermentation process, are filamentous biomass and riboflavin. In this work an optimal pH values for the best accumulating biomass and riboflavin environment is defined and positive effects on increasing the intensity of mixing on yield of the desired product are shown. For biomass accumulation it is recommended to create a nutrient medium with pH 5,5-6,0 and use low mixing level. To maximize riboflavin biosynthesis is necessary pH 7,5 and intensive mixing. For the first time shows the rate of riboflavin synthesis by E.ashbyi strain depending on sources of carbon and nitrogen supply, which is especially important for the further improvement of production technology of riboflavin. The best results for riboflavin synthesis were shown to sorbitol, fructose, galactose and methionine, arginine, peptone. The most promising complex environment is unhopped beer wort.